Damage To Brick-Walled Buildings And Effective Ways To Strengthen Brick Structures When Baratarafing Them (Texas Journal of Engineering and Technology, 2024)
This article examines the causes of defects in brick walls, research into the actual operation of structural elements, and improvement of methods for the reliable elimination of cracks, deformations, damage and distortions that arise when assessing their technical condition